Gallium-67 SPECT/CT and diffusion-weighted MRI in the palatal tumor: report of a rare case with adenocarcinoma not otherwise specified - Ayako Kameta; Yoshihiko Sasaki; Yoriaki Kanri; Yasuo Okada; Ichiro Ogura (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Adenocarcinoma not otherwise specified (NOS) is an uncommon malignant minor salivary gland tumor. We report gallium-67 SPECT/CT and diffusion-weighted MRI (DWI) in the palatal tumor, especially a rare case with adenocarcinoma NOS. Case presentation An 85-year-old female patient presented with swelling on the palate within 3 months. DWI and apparent diffusion coefficient (ADC) maps indicated high and low signal intensities on the lesion, respectively. ADC value of the lesion was 0.58 × 10–3 mm2s−1. Gallium-67 SPECT/CT showed increased uptake on the lesion and no metastasis. The maximum SUV for the palatal lesion was 7.36. Histopathological diagnosis by a biopsy was adenocarcinoma NOS. Conclusion The gallium-67 SPECT/CT and DWI should be effective for assessment of the palatal tumor.